Endocannabinoids - Suchopár, Josef; Laštůvka, Zdeněk; Mašková, Simona; Alblová, Miroslava; Pařízek, Antonín (Ceska gynekologie, 2021)
OBJECTIVE: Overview of current knowledge in the field of the endocannabinoid system with emphasis on the relationships between endocannabinoids and exocannabinoids. The endocannabinoid system consists of cannabinoid receptors 1 and 2, ligands of these receptors, especially two classical; endocannabinoids N-arachidonoylethanolamine (anandamide) and 2-arachidonoyl-glycerol. Transport systems that ensure the entry of endocannabinoids into cells, where they are degraded by fatty acid amide hydrolase or monoacylglycerol lipase. The endocannabinoid system is a signaling pathway for the regulation of a number of physiological or pathological conditions. So far, it is one of the less explored ways of regulation, as evidenced by the recent explosive increase in the number of published works. Dysregulation of endocannabinoid systems is a possible cause of many diseases. It can occur both in the genetic polymorphism of its individual components, but also in therapy with certain drugs or natural substances, typically cannabinoids. Due to the wide overlap of the regulation of physiological functions by the endocannabinoid system, a considerable number of drugs are being developed, the aim of which is to correct the dysregulation of the endocannabinoid system. CONCLUSION: The endocannabinoid system is one of the most important regulatory systems with a very broad intervention in physiological and pathological conditions. The resulting specific regulations intersect the interplay of many enzymes involved in the production and degradation of endocannabinoids, transport systems involved in the entry of endocannabinoids into cells, cannabinoid receptors and exogenous cannabinoids, or natural substances acting at various sites in the endocannabinoid system. Knowledge in this area can contribute to improving health care and increasing the safety of its provision.
Keywords: receptory kanabinoidní; kanabinoidy; fatty acid amide hydrolases; cannabinoid receptor; 2-arachidoyl glycerol; endokanabinoidy; lipase for monoacylglycerols; Cannabinoids; Humans; Endocannabinoids; anandamide; Receptors, Cannabinoid; fatty acid binding proteins; lidé